Sewage Water Treatment And Its Effect On The Cleanliness Of Water: A Review From Islamic And Science Perspective - Mohd Mahyeddin Mohd Salleh; Yasmin Hanani Mohd Safian; Syaza Azhari; Hussein Azemi Ahmad Thaidi (Jabatan Fiqh dan Usul, Akademi Pengajian Islam, University of Malaya, 2024)
Indexed by MyCite